2008
DOI: 10.1590/s1807-59322008000500007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Health-Related Quality of Life in Elderly Patients According to the Type of Hip Fracture: Femoral Neck or Trochanteric

Abstract: OBJECTIVE: To evaluate the effect the type of hip fracture (femoral neck or trochanteric) has on the Health-Related Quality of Life of elderly subjects. METHODS: Forty-five patients with hip fractures (mean 74.30 ± 7.12 years), 24 with a femoral neck fracture and 21 with a trochanteric fracture, completed the 36-item Short Form Health Survey (SF-36) at baseline and four months after fracture. The Health-Related Quality of Life scores were compared according to fracture type, undisplaced and displaced femoral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
15
0
9
Order By: Relevance
“…[13][14][15][16][17] The literature also shows a high morbidity related to femoral fractures, with some degree of physical limitation around 4 months after a fracture. 18 In a prospective study of 68 patients, only 32.56% reacquired the walking capacity and 27.9% of the previously independent patients needed special care. 7 As a condition of high prevalence among the elderly, whose treatment is essentially surgery 5 and a long hospital stay, femoral fracture entails high costs.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] The literature also shows a high morbidity related to femoral fractures, with some degree of physical limitation around 4 months after a fracture. 18 In a prospective study of 68 patients, only 32.56% reacquired the walking capacity and 27.9% of the previously independent patients needed special care. 7 As a condition of high prevalence among the elderly, whose treatment is essentially surgery 5 and a long hospital stay, femoral fracture entails high costs.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies found that 3–4 months after a fracture, partial recovery was observed in the SF‐12 scores of physical and mental measures. However, another study found that after 1–2 years, the perceived health‐related quality of life approached the level prior to the fracture (Mendonca et al, ). It seems that in the period after a fall, the effect of a fracture is not restricted to the anatomical sphere but finds expression in additional aspects of life.…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is another important OM following hip fractures (Aitken and Bohannon, ), and older women continuing to report inferior quality of life in the years after the break (Cranney et al, ). Hip fractures were found to correlate with a more negative perception of health‐related quality of life (Hallberg et al, ; Ekstrom et al, ), with older women continuing to report inferior quality of life in the first year after the break (Boonen et al, ; Cranney et al, ; Mendonca et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies in the English literature focused on quality of life and used the SF-36 for outcome evaluation after operatively treated pertrochanteric fractures [12,13]. Mattson et al [12] reported 57 patients with unstable pertrochanteric fractures treated by DHS with slightly better results in general health, social functioning and mental health subscales on the SF-36 at six months postoperatively compared to our cohort.…”
Section: Discussionmentioning
confidence: 81%